Increased adipose tissue lymphatic vessel density inhibits thermogenesis through elevated neurotensin levels - Phan, Thien T.; Chakraborty, Adri; Tatum, Madison A.; Lima-Orellana, Ana; Reyna, Andrea J.; Rutkowski, Joseph M. (Frontiers in Cell and Developmental Biology, 2023)
During cold exposure, white adipose tissue can remodel to dissipate energy as heat under cold similar to thermogenic brown adipose tissue. This “browning” and the regulation of body temperature is under the control of neural and hormonal signaling. It was recently discovered that neurotensin, a small neuropeptide, not only acts to inhibit thermogenesis, but also that lymphatic vessels may be a surprisingly potent source of neurotensin production. We hypothesized that the induction of adipose tissue lymphangiogenesis would therefore increase tissue neurotensin levels and impair thermogenesis. Methods: We utilized AdipoVD mice that have inducible expression of vascular endothelial growth factor (VEGF)-D, a potent lymphangiogenic stimulator, specifically in adipose tissue. Overexpression of VEGF-D induced significant lymphangiogenesis in both white and brown adipose tissues of AdipoVD mice. Results: Obese Adipo-VD mice demonstrated no differences in adipose morphology or browning under room temperature conditions compared to controls but did express significantly higher levels of neurotensin in their adipose tissues. Upon acute cold exposure, AdipoVD mice were markedly cold intolerant; inhibition of neurotensin signaling ameliorated this cold intolerance as AdipoVD mice were then able to maintain body temperature on cold challenge equivalent to their littermates. Conclusion: In total, these data demonstrate that adipose tissue lymphatic vessels are a potent paracrine source of neurotensin and that lymphangiogenesis therefore impairs the tissues’ thermogenic ability.